Energy production from steam gasification processes and parameters that contemplate in biomass gasifier – A review. (February 2020) - Singh Siwal, Samarjeet; Zhang, Qibo; Sun, Changbin; Thakur, Sourbh; Kumar Gupta, Vijai; Kumar Thakur, Vijay
Graphical abstract: Highlights: Gasification as a multipurpose thermo-chemical conversion proces. Comparison of the conventional and new gasification technologies. Different zones of steam gasification of biomass. Different parameters considered in the steam gasification studied. Abstract: The transformation of biomass using steam gasification is a chemical route to facilitate changes in organic or residue supported carbonaceous substances addicted to carbon mono-oxide, hydrogen including carbon-di-oxide, etc. However, to commercialize the method of steam gasification, the hurdles persist during the gasification as well as downstream processing. This article delivers a summary of the different approaches that are described in the previous studies to achieve H2 refinement and adaptation within the gasifier system. These include advanced aspects in the research and development of biomass gasification (alike advancements under the gasification operation). The upshot of diverse operating conditions like steam flow rate, operating temperature, moisture content, gasifier agents, residence time, biomass to air, steam to biomass, equivalence ratio, etc. towards the execution of biomass gasifier. This review accomplishes that the interdependence of several issues must be considered in point to optimise the producer gas.